Nội dung text 10. INVERSE TRIGANOMETRIC FUNCTIONS MEDIUM ANS.pdf
1. (b) 3 3 sin sin 1 = − − − − − 2 sin 2 1 x 2. (c) o o o sec [sec( 30 )] sec (sec 30 ) 30 1 1 − = = − − . 3. (c) 2 3 3 sin 3 5 sin sin 1 1 = − = − − − 4. (d) The principal vlaue of )] 3 2 sin [sin( 1 − − = 3 3 sin sin 1 = − 5. (d) Put 2 1 cot 2 1 cot 1 = = − . 5 2 sin = Put = − x 1 cos then x = cos Also 3 5 , cos 5 2 tan = x = = 6. (a) sin [sin( 600 )] 1 o = − − = sin [ sin(360 240 )] 1 − + − sin [ sin 240 ] 1 o = − − sin [ sin(180 60 )] 1 o o = − + − o sin sin60 −1 = 3 3 sin sin 1 = = − 7. (a) + − − 3 5 sin sin 3 5 cos cos 1 1 + − = − − − 3 sin sin 2 3 cos cos 2 1 1 0 3 3 = − = 8. (a) Given equation is 6 11 2 cos sin 1 1 + = − − x x 6 11 cos (cos sin ) 1 1 1 + + = − − − x x x 6 2 11 cos 1 = − − x 3 4 cos 1 = − x , which is not possible as − cos 0, 1 x . 9. (b) 3 2 sin sin 1 1 + = − − x y 3 2 cos 2 cos 2 1 1 − + − = − − x y 3 cos cos 1 1 + = − − x y 10. (b) We know that , | | 1 2 sin cos 1 1 + = − − y y y According to question, .......... ... 2 4 .......... 2 4 4 6 2 2 3 − + − = − + − x x x x x x , ( 0 | | 2 2 1 2 1 2 2 + = + x x x x x ) 2 2 2 2 x x x x + = + 3 2 3 2x + x = 2x + x 2 x = x 0 (1 ) 0 0 2 x − x = x − x = x = and x = 1, but x 0. So, x =1 11. (b) 2 2 sin cot 1 1 = + − − x x = − − 5 1 cos 2 1 cot 1 1 5 2 1 sin cos 1 1 + = − − x ; Clearly, 5 1 x = 12. (d) sin(cot ) 1 x − = + − 2 1 1 1 sin sin x = 2 1 1 + x 13. (c) 2 tan ( 1) sin 1 1 1 2 + + + + = − − x x x x tan ( 1) 1 + − x x is defined, when x(x + 1) 0 ........(i) sin 1 1 2 + + − x x is defined, when 0 x(x + 1) + 1 1 or 0 x(x + 1) 0 ........(ii) From (i) and (ii), x(x + 1) = 0 or x = 0 and –1. Hence, number of solutions is 2 14. (d) + − − 13 3 cos 5 3 tan sin 1 1 = + − − 3 2 tan 4 3 tan tan 1 1 = − + − 3 2 . 4 3 1 3 2 4 3 tan tan 1 = − 6 12 12 17 tan tan 1 = 6 17 15. (b) 4 tan 1 3 1 . 2 1 1 3 1 2 1 tan 3 1 tan 2 1 tan 1 1 1 1 = = − + + = − − − − 16. (c) + = + = − + − − − − − 9 5 4 2 sin 9 1 1 3 2 9 4 1 3 1 sin 3 2 sin 3 1 sin 1 1 1 1 Therefore, 9 5 + 4 2 x = 17. (b) 1 2
cot 3 5 1 5 1 1 cot 3 cot 5 1 sin−1 −1 −1 −1 + − + = = 4 cot (1) 3 2 2 3 1 cot (2) cot (3) cot 1 1 1 1 = = + − + = − − − − 18. (d) Given, 13 12 cos 5 3 sin sin −1 −1 −1 C = + 13 5 sin 5 3 sin sin −1 −1 −1 C = + = − + − − 25 9 1 13 5 169 25 1 5 3 sin 1 65 56 65 56 sin 1 = = − C 19. (c) 16 63 tan 4 3 tan 5 12 tan −1 −1 −1 + + = 16 63 tan 20 36 48 15 tan −1 −1 + − + + ( xy 1 ) = − + = − − 16 63 tan 16 63 tan 1 1 20. (a) = − + − − 25 16 1 3 1 9 1 1 5 4 sin 1 = + = + − − 15 8 2 3 sin 15 3 15 8 2 sin 1 1 Since 2 1, 15 8 2 3 + 2 ( ) 3 1 sin 5 2 4 sin 2 1 1 = − = − + − − − 21. (a) + = − − 3 cos 2 cos 1 x 1 y cos 9 1 4 1 3 . 2 2 2 = − − − x y x y ( 6 cos ) (4 )(9 ) 2 2 2 xy − = − x − y 2 2 2 2 9x − 12 xy cos + 4y = 36(1 − cos ) = 36 sin 22. (b) x x 1 1 1 sin 2 3 sin 2 sin − − − = − = − − − − 4 3 . 1 1 2 3 sin 1 2 x x 2 1 2 3 2 2 x x = − x − (1 ) 4 3 2 5 2 2 x x = − or 28 3 2 x = 7 3 2 1 28 3 x = = , (not 7 3 2 1 − ) 23. (d) Since, 2 1 1 1 2 2 tan tan x x x − = − − 25 1 1 5 2 2 tan 5 1 2 2 tan 5 1 4 tan 1 1 1 − = = − − − 576 100 1 24 20 tan 24 10 2 tan 1 1 − = = − − 119 120 tan−1 = So, 239 1 tan 119 120 tan 239 1 tan 5 1 4 tan−1 −1 −1 −1 − = − 239 1 . 119 120 1 239 1 119 120 tan 1 + − = − (119 239 ) 120 (120 239 ) 119 tan 1 + − = − 4 tan 1 1 = = − 24. (d) If x = −1, LHS = , 2 RHS = − 2 2 . So, the fomula does not hold. If x −1, the angle on the LHS is in the second quadrant while the angle on the RHS is 2 (angle in the fourth quadrant), which cannot be equal. If x 1, the angle on the LHS is in the second quadrant while the angle on the RHS is 2 (angle in the first quadrant) and these two may be equal. If −1 x 0 , the angle on the LHS is positive and that on the RHS is negative and the two cannot be equal 25. (a) Let x = tan . Then sin (sin 2 ) 1 tan 2 tan sin 1 2 sin 1 2 1 2 1 − − − = + = + x x 2 sin (sin 2 ) 1 2 2 tan sin 1 2 1 1 − − − = + + + x x x If 2 1 1 1 2 , 2 tan sin 2 2 2 x x x + − + − − = + = − x 1 2 2 4 tan independent of x. If 2 1 1 1 2 , 2 tan sin 2 2 2 x x x + − − + − − = 2 sin [sin( 2)] 2 2 1 + − = + − − = = independent of x. − 4 , 4 but 4 3 , 4 and from the principal value of x 1 tan − . − 2 , 2 . Hence, 2 , 4 2 , 4 = + + − − 2 1 1 1 2 tan sin x x x . Also at = + = + = + = + − − − 2 2 sin 1 4 2. 1 2 , 2 tan sin 4 1 2 1 1 x x x . The given function = = constant if 2 , 4 . i.e., x [1,+ ) 26. (d) If we denote x 1 cos− by y, then Since − 0 cos x 1 0 2y 2 .........(1) Also since 2 sin 2x 1 x 2 1 2 − − −
( ) 2 sin sin 2y 2 1 − − 2 2y 2 − ...........(2) From (1) and (2) we find 2 0 2y 4 0 y 4 0 cos x 1 − which holds if x 1 2 1 27. (a) Given equation can be written as tan–1 (x – 1) + tan–1 (x + 1) = tan–1 3x – tan–1 x tan–1 1 (x 1)(x 1) x 1 x 1 − − + − + + = tan–1 2 1 3x 3x x + − 2 2 1 3x 2x 2 x 2x + = − x + 3x3 = 2x – x 3 4x3 – x = 0 x(4x2 – 1) = 0 x = 0, x = ± 1⁄2 none of which satisfies 1 < x < 2 28. (b) (cot–1 x – 1) (cot–1 x – 2) > 0 x < cot 2 or x > cot 1 (cot–1 x is a decreasing function) 29. (d) tan cos–1 5 4 = 4 3 , tan tan–1 3 2 = 3 2 expression in the question = 1 3/ 4 2 / 3 3/ 4 2 / 3 − + = 6 17 Choice (d) is correct. 30. (b) By tan (A + B + C) formula tan (tan–1 + tan–1 + tan–1 ) = tan − + + − − − − − − − − − 1 1 1 1 1 1 1 1 1 tan tan tan tan tan (tan )(tan )tan = tan 1 3 ( m) ( m) − − − − = tan 0 = 0 tan–1 + tan–1 + tan–1 = n 31. (a) tan2 (sin–1 x) > 1 4 < sin–1 x < 2 or – 2 < sin–1 x < – 4 x ,1 2 1 or x − − 2 1 1, x − − 2 1 1, , 1 2 1 Hence (A) is the correct answer. 32. (b) cos (2cos–1 x + sin–1 x) = cos = –sin (cos–1 x) = – sin(sin–1 ) = – 2 1− x = – 2 6 1 1 − = – 36 35 = – 6 35 . 33. (d) > 2tan–1x 0 2 > tan–1x 0 also 1 + x2 1 – x 2 x 0 34. (b) x x x x 1 1 1 1 tan 2 sin cos tan − − − − = + − = − We know 2 tan 2 1 − − x 4 tan 2 0 2 tan 2 1 1 − − − − − x x 35. (a) We have = − − − − 2 2 2 2 1 cos . 1 1 b y a x b y a x 1 1 cos 2 2 2 2 = − − − b y a x ab xy 2 2 2 2 2 2 2 2 2 cos 1 a b x y b y a x ab xy = − − + − 2 2 2 2 2 2 2 2 2 2 2 2 2 cos 1 2 cos a b x y b y a x ab xy a b x y + − = − − + 2 2 2 2 2 2 cos 1 cos sin 2 − + = − = b y ab xy a x 36. (a) a b c a b c ca b a b c b c a a b c ( ) tan ( ) tan ( ) tan 1 1 1 + + + + + + + + = − − − Let abc a b c s + + = 2 1 2 2 1 2 2 1 2 2 tan a s tan b s tan c s − − − = + + tan ( ) tan ( ) tan ( ) 1 1 1 as bs cs − − − = + + − − − + + − = − 2 2 2 3 1 1 tan abs bcs cas as bs cs abcs 0 1 ( ) ( ) tan 2 2 = − + + + + − = ab bc ca s a b c abcs s [ ( )] 2 abcs = a + b + c Trick : Since it is an identity so it will be true for any value of a,b,c. Let a = b = c = 1 then tan 3 tan 3 tan 3 , 1 1 1 = + + = − − − tan = 0 37. (d) + − x 1 cos 2 2 1− x
2 tan (cos ) 1 x − tan (cos ec ) 1 2 x − = x x x x x x 2 2 2 1 2 1 sin 1 sin 2cos sin 1 tan 1 cos 2cos tan = = − − − 3 2 cos 1 x = x = 38. (c) x x 1 1 sin 2 tan − − = 2 1 1 1 2 sin sin x x x + = − − x x x = + 2 1 2 0 3 x − x = x(x + 1)(x −1) = 0 x = {−1,1, 0} 39. (b) + − − − x x 1 1 2 tan 2 tan 2 sin = 2 sin = 1 40. (d) Put a = tan,b = tan and x = tan, then reduced form is sin (sin 2 ) cos (cos 2 ) tan (tan 2 ) 1 1 1 − − − − = 2 − 2 = 2 − = Taking tan on both sides, we get tan( − ) = tan tan 1 tan .tan tan tan = + − Substituting these values, we get x ab a b = + − 1 41. (d) − − = − − − − tan (1) 25 1 1 5 2 tan tan 5 4 1 tan 2 tan 1 1 1 = 17 7 12 5 1 1 12 5 tan (1) tan.tan 12 5 tan tan 1 1 1 − = + − = − − − − 42. (c) 99 1 tan 70 1 tan 5 1 4 tan−1 −1 −1 − + = 99 1 tan 70 1 tan 25 1 1 5 2 2 tan −1 −1 −1 − + − = 99 1 tan 70 1 tan 12 5 2 tan−1 −1 −1 − + = 99 1 tan 70 1 tan 144 25 1 6 5 tan −1 −1 −1 − + − = 99 1 tan 70 1 tan 119 120 tan−1 −1 −1 − + = + − + − − 70 1 . 99 1 1 70 1 99 1 tan 119 120 tan 1 1 = + − − − 6931 29 tan 119 120 tan 1 1 = 239 1 tan 119 120 tan 6931 29 tan 119 120 tan−1 −1 −1 −1 − = − = 4 tan (1) 239 1 119 120 1 239 1 119 120 tan 1 1 = = + − − − 43. (b) cos[tan (2 2)] 3 1 sin 2 tan−1 −1 + = cos[tan (2 2)] 9 1 1 3 2 sin tan −1 −1 + − cos[tan 2 2] 4 3 sin tan−1 −1 + = = 15 14 3 1 5 3 3 1 cos cos 5 3 sin sin 1 1 = + = + − − 44. (b) Let b a b a = = − cos cos 1 + − + − − b a b 1 a 1 cos 2 1 4 cos tan 2 1 4 tan = t t t t + − + − + 1 1 1 1 , where 2 tan t = a b t t 2 cos 2 1 (1 ) 2 2 2 = = − + = 45. (b) tan 3 1 tan tan −1 −1 −1 + = y x or y 1 tan −1 = x 1 1 tan 3 tan − − − or x x y 1 3 3 tan 1 tan 1 1 + − = − − x x y − + = 3 1 3 As x, y are positive integers, x =1 , 2 and corresponding y = 2, 7 Solutions are (x, y) = (1, 2),(2,7) 46. (d) sin x cos x tan x −1 −1 −1 = + − tan x 2 −1 − = and since 4 0 tan x 1 − when 0 x 1 we fined 4 2 47. (d) The given expression is equal to ( ) + + = − − − sin x 2 cos cos x sin x cos 1 1 1 = ( ) 5 1 sin sin x x 1 − = − = − − 48. (c) The given expression is equal to − − 6 tan 3 2 tan cos ec 1 = 6 3 2 x 3 1 2 tan 3 1 3 2 2 tan 1 1 = = = − − −